La ceramica bassomedievale a Pisa e San Genesio (San Miniato-Pi) : città e campagna a confronto - Fatighenti, Beatrice (Archaeopress, 2016)
This title presents the study of pottery in two medieval contexts, Pisa (a city) and San Genesio (a central place in the Arno Valley).